The politics of Islam in contemporary Malaysia - Kamarulnizam Abdullah (Series on Malaysian politics, 2003)
This book focuses on two major Malay politic parties, UMNO and PAS, two major dakwah movements, ABIM and Al-Arqam, to analyse and to examine their impact on Malaysian politics. This book explores the role of Islam in Malay society and politics and tries to establish a systematic linkage between Islam and Malay unity.